Contract law - Elliott, Catherine; Quinn, Frances (Harlow : Pearson Education Limited, 2020)
This book provides a clear and accessible introduction to contract law, making it ideal for students and legal professionals who need a solid foundation in the subject. It covers essential contract law principles in a structured and engaging manner, using real-world examples to illustrate key concepts.